Occurrence of imposes in Manila clam (Venerupis philippinarum Adams & Reeve 1850) from Lahug Market, Cebu City, Cebu - Benedicto, Jan Dominique R. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2021)
Pseudohermaphrodism or imposex is a widespread phenomenon among molluscs characterized by the superimposition of non-functional male sex organs on females. This is mainly caused by exposure to Tributyltin (TBT) which is the most used antifouling agent incorporated in paints for the underwater hull of large boats. Tributyltin compounds are known to cause harmful effects to nontarget organisms in the aquatic environment. This study aimed to evaluate the occurrence of imposex in Manila clams obtained from the market using indices, namely, Incidence of Imposex (IOI), Relative Penis Size Index (RPSI), and Conversion of Potential Female to Imposex Index (CPFII). The calculated IOI was 7.46%, RPSI at 7.66%, and CPFII at 6.94%. This study also correlated the weight and shell length of male and female sample clams, and compared penis and pseudopenis lengths. From the 100 randomly chosen fresh samples, 67 were females and 33 were males. Mean penis length of males was higher at 1.04cm and only 0.44 cm for imposex females. It was found that male clams have higher mean shell length and weight at 4.148 cm and 35.166 g respectively. Length and weight also has a positive correlation at r=0.771. The presence of imposex female in the Manila clams suggest that the samples obtained from the market might have been exposed to TBT.